2019
DOI: 10.1007/s10815-019-01401-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s morbid conditions are associated with decreased odds of live birth in the first IVF/ICSI treatment: a retrospective single-center study

Abstract: Purpose The present study aims to ascertain whether there is a causal relationship between women's disease conditions present at the starting time of the first intended oocyte retrieval cycle and IVF/ICSI outcomes, primarily odds of live birth in the first IVF/ ICSI treatment. Methods This is a retrospective study of infertile healthy and diseased women that had a live birth and/or exhibited a complete first oocyte retrieval cycle. Generalized Estimating Equations (GEE) models were applied to adjust standard e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…GEE models allow for analysis of repeated measurements or other correlated observations such as clustered data, especially when they are binary or in the form of counts [13]. In a previous study [14], we found that the goodness-of-fit of GEE models improved on most occasions after adjusting standard errors for the potential correlation among women exhibiting the same infertility etiology. Therefore, variables were arranged in a hierarchical two-level structure with women starting ovarian stimulation clustered within female infertility etiology.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…GEE models allow for analysis of repeated measurements or other correlated observations such as clustered data, especially when they are binary or in the form of counts [13]. In a previous study [14], we found that the goodness-of-fit of GEE models improved on most occasions after adjusting standard errors for the potential correlation among women exhibiting the same infertility etiology. Therefore, variables were arranged in a hierarchical two-level structure with women starting ovarian stimulation clustered within female infertility etiology.…”
Section: Discussionmentioning
confidence: 82%
“…Only ICD-10 chapters with sample sizes ≥ 10 women/men were included in the study as distinct groups. ICD-10 chapters with sample sizes < 10 women/men were combined in a single "catch-all" group called "other diseases" [14] g ICD-10 chapters: "Diseases of the blood and blood-forming organs and certain disorders involving the immune mechanism" (n = 23), "Endocrine, nutritional and metabolic diseases" (n = 187), "Mental and behavioral disorders" (n = 17), "Diseases of the nervous system" (n = 22), "Diseases of the circulatory system" (n = 18), "Diseases of the respiratory system" (n = 23), "Diseases of the digestive system" (n = 20), "Diseases of the musculoskeletal system and connective tissue" (n = 17), and "other diseases" (n = 30) h ICD-10 chapters: "Endocrine, nutritional and metabolic diseases" (n = 33), "Diseases of the circulatory system" (n = 40), "Diseases of the respiratory system" (n = 27), "Diseases of the digestive system" (n = 23), "Diseases of the genitourinary system" (n = 15), and "other diseases" (n = 68)…”
Section: Resultsmentioning
confidence: 99%
“…Values are means and SDs in parenthesis b Number of cigarettes smoked per day for the 3 months before starting the first intended oocyte retrieval cycle c Values are percentages d Medical conditions were assessed following the International Statistical Classification of Diseases and Related Health Problems 10th Revision (ICD-10 Version 2016)[14] …”
mentioning
confidence: 99%
“…A paper from 2019 examined very broad categories of women with chronic diseases and found lower odds of a live birth, compared to healthy women. 9 The study included 1291 women receiving ART and the underlying diseases for these women were distributed across all ICD10 categories. The studies included in this review points towards a more varied and complex picture.…”
Section: Discussionmentioning
confidence: 99%
“…Seven papers were excluded as they did not include an external reference group, and one paper was excluded because the analyses were based on overall chapters from the International Classification of Disease (and not the specific diseases of interest). 9 The overview is given in Figure 2 (PRISMA flow chart). A total of 13 papers were thus eligible for the review criteria.…”
Section: Methodsmentioning
confidence: 99%